Your question makes no sense could you give a better description please
Answer: y= x/5 -6
Step-by-step explanation: gradient= 1/5...(m1m2=-1)
y-y1=M(x-x1)
y-8=1/5(x-10)
5y-40=x-10
y=x/5-6
In your question where to explain how the raising a quotient to power is similar to raising a product to a power. Form me the best explanation to this statement is because the variable with a exponent of positive is equals to its exponent over its variable.
Step-by-step explanation:
it's close to 6
.................